A Novel Four-Way Complex Variant Translocation Involving Chromosome 46,XY,t(4;9;19;22)(q25:q34;p13.3;q11.2) in a Chronic Myeloid Leukemia Patient - Asif, Muhammad; Jamal, Mohammad Sarwar; Khan, Abdul Rehman; Naseer, Muhammad Imran; Hussain, Abrar; Choudhry, Hani; Malik, Arif; Khan, Shahida Aziz; Mahmoud, Maged Mostafa; Ali, Ashraf; Iram, Saima; Kamran, Kashif; et al. (Frontiers in Oncology, 2016)
Philadelphia (Ph) chromosome (9; 22)(q34;q11) is well established in more than 90% of chronic myeloid leukemia (CML) patients and the remaining 5-8% CML patients show variant and complex translocations, with the involvement of third, fourth or fifth chromosome other then 9;22. However, in very rare cases the fourth chromosome is involved. Here, we find a novel case of four way Ph+ chromosome translocation involving 46,XY, t(4;9;19;22)(q25:q34;p13.3;q11.2) with CML in the chronic phase. Complete blood cell count of CML patient was carried out to obtain total leukocytes count, hemoglobin and platelets. Fluorescence In situ hybridization technique was used for the identification of BCR-ABL fusion gene and cryptogenic test for the confirmation of Ph (9; 22)(q34;q11) and the mechanism of variant translocation in the bone marrow. The patient is successfully treated with Imatinib mesylate (Gleevec) with 400mg/day dose. We observed a significant decrease in WBC count after 48 months follow up 11.7 x109/L. Patient started feeling better generally. There was a reduction in the swelling of the body, fatigue and anxiety.